The Current Status of Kuhl’s Pipistrelle, Pipistrellus kuhlii (Chiroptera, Vespertilionidae), in the Central Forest-Steppe of Ukraine - Bilushenko, A.A. (Вестник зоологии, 2013)
Based on our own fieldwork the faunistic status of the Kuhl’s pipistrelle for the studied region was established. The expansion of Pipistrellus kuhlii (Kuhl, 1817) in the central part of the forest-steppe zone of Ukraine was confirmed. The paper represents data on the findings of this species and its prevalence, occurrence, describes biology and flight activity throughout the year in the studied territory.